Meritocracy and Legal Certainty in Notary Appointment Justice: Meritokrasi dan Kepastian Hukum dalam Penunjukan Notaris - Aminah Aminah; Indrati Rini; Habib Adjie (Academia Open, 2025)
General background: The selection and appointment of notaries in Indonesia reveal a persistent tension between achieving justice and ensuring legal certainty. Specific background: While existing laws outline clear administrative procedures, they often overlook the meritocratic principles necessary to ensure that notaries possess the competence, integrity, and moral quality required for public trust. Knowledge gap: Previous studies have emphasized educational quality and regulatory inconsistencies but have not addressed the philosophical conflict between meritocracy and legal certainty. Aims: This study aims to examine how the philosophy of justice can guide the integration of meritocracy into the framework governing notary appointments in Indonesia. Results: The findings show that current legal mechanisms prioritize procedural clarity but fail to ensure substantive fairness, resulting in appointments that meet formal criteria yet lack ethical and professional depth. Novelty: This study introduces a philosophical synthesis that harmonizes legal formalism with moral justice by positioning meritocracy as an essential component of legal legitimacy. Implications: The study highlights the need for legal reform to embed transparent, merit-based evaluation systems that uphold justice, strengthen institutional credibility, and align positive law with the ethical ideals of fairness and societal trust. Highlights: Highlights the philosophical balance between meritocracy and legal certainty in notary appointments. Reveals the weakness of current legal procedures in ensuring substantive justice. Proposes integrating merit-based evaluation to enhance fairness and legal legitimacy. Keywords: Notary, Meritocracy, Legal Certainty, Philosophy of Justice, Law Reform